An Analysis of Turn-Taking Strategies used in EFL Classroom Interaction at Universitas Muslim Maros - Haryanto Atmowardoyo; Nurul Ainul (ITEKES Permata Ilmu Maros, 2025)
The main aims of this research are to identify turn-taking strategies in students' classroom interactions, to describe dominant strategies, and to describe the impact of turn-taking strategies. This research used a qualitative descriptive design. Students in English Department at Maros Muslim University were chosen as the research subjects. Data were collected through video recordings and structured interviews. The results of this research showed that: (1) Holding the turn is dominant strategies because, between lecturer and students in the classroom interaction more used Filled pauses and Verbal fillers. (2) There are three Turn Taking used by students at Universitas Muslim Maros are: they are taking the turn strategy, holding the turn, and yielding the turn. In other words, filled pauses, verbal fillers, lexical pauses, silent pauses. (3). The impacts of turn taking strategy are; To smooth communication, the use of Indonesian language, challenges, lecturer's explanation, lecturer and student’s interaction.